A new species of Nemoura (Plecoptera: Nemouridae) from South of the Russian Far East - Teslenko, Valentina A. (Zootaxa, 2015)
A new species of Plecoptera from the Nemoura ovocercia group, Nemoura khasanensis sp. n. from the Primorsky Region, south of the Russian Far East, is described and illustrated. The diagnostic characters for separation from other members of the oviocercia group are provided.